Meningkatkan Aktivitas Keterampilan Menulis Dalam Bentuk Poop Up Book Mel Menggunakan Model Project Based Learning Kombinasi Cooperative Integrated Reading And Composition Dan Talking Stick - Widyaningsih Lilik Tri; Mahmuddin Mahmuddin (Jurnal Pendidikan Sosial Dan Konseling, 2024)
An obstacle in research is the lack of quality writing activities from students, which has a negative impact on achieving their learning outcomes in Indonesian language subjects. The reasons behind this are because learning only flows from one direction, the focus in learning Indonesian is on grammar, and there is a lack of use of various models in learning. This research applies the Classroom Action Research (PTK) methodology by holding 4 meeting sessions. The data used is quality data, obtained through observations of teacher activities, student activities, and student writing abilities. These findings show that teachers have good quality in learning activities at the initial stage of meetings I-III, getting the title "very good" at the fourth meeting. Student participation at meetings I-IV has increased significantly until it reaches a very high level of participation at meeting IV, from 25% to 94%. Likewise with evaluation of affective, cognitive and physical skill aspects. Students scored between 25% to 81% in the emotional aspect. Furthermore, in terms of understanding, students achieved a percentage between 25 to 88%. Furthermore, in terms of physical abilities, students get results between 31% and 88%.